Identification and characterization of Bacillus thuringiensis and other Bacillus cereus group isolates from spinach by whole genome sequencing - Zhao, Xingchen; Zervas, Athanasios; Hendriks, Marc; Rajkovic, Andreja; van Overbeek, Leo; Hendriksen, Niels Bohse; Uyttendaele, Mieke (Frontiers in Microbiology, 2022)
Bacillus thuringiensis (Bt), used as a biological control agent (BCA), can persist on plants, and from there can be introduced into the final food product. In routine food safety diagnostics, these Bt residues cannot be distinguished from natural populations of Bacillus cereus present in plants and all are enumerated as ‘presumptive B. cereus’. In this study, information on eventual use of Bt biopesticides, brand, application times and intervals provided by three food processing companies in Belgium, were integrated with quantitative data on presumptive B. cereus measured from fresh to frozen food products. This information together with data on genomic similarity obtained via whole genome sequencing (WGS) and cry gene profiling using a quantitative real-time PCR (qPCR) assay, confirmed that six out of eleven Bt isolates originated from the applied Bt biocontrol products. These identified Bt strains were shown to carry enterotoxin genes (nhe, hbl, cytK-2) and express Hbl enterotoxin in vitro. It was also noted that these Bt biopesticide strains showed no growth at standard refrigeration temperatures and a low or moderate biofilm-forming ability and cytotoxic activity. Our results also showed that the use of Bt as a BCA on spinach plants in the field led to higher residual counts of Bt in spinach (fresh or frozen) in the food supply chain, but the residual counts exceeding at present commonly assumed safety limit of 105 CFU/g was only found in one fresh spinach sample. It is therefore recommended to establish a pre-harvest interval for Bt biopesticide application in the field to lower the likelihood of noncompliance to the generic B. cereus safety limit. Furthermore, WGS was found to be the best way to identify Bt biopesticide isolates at the strain level for foodborne outbreaks and clinical surveillance. The developed qPCR assay for screening on the presence of cry genes in presumptive B. cereus can be applied as a rapid routine test as an amendment to the already existing test on Bt crystal proteins determined via phase-contrast microscopy.